Do investors flip less in bookbuilding than in auction IPOs? - Neupane, Suman; Marshall, Andrew; Paudyal, Krishna; Thapa, Chandra (Journal of Corporate Finance, 2017)
Using a regime change setting, this paper examines whether investors flip less in bookbuilding than in auction initial public offerings (IPOs). Based on bookbuilding theory, we posit that the ability to control allocation flexibility in the bookbuilding mechanism should enable underwriters to avoid flippers and target long-term investors. Consistent with this prediction, we find that both frequent and non-frequent investors flip significantly less in bookbuilding IPOs. We also find that the influence of underwriter reputation is stronger in the bookbuilding regime, with frequent investors flipping considerably less in IPOs that are managed by high reputation underwriters in bookbuilding IPOs compared to auction IPOs. The results highlight the benefits of allocation discretion, which allows underwriters to influence investors' behavior as well as use non-bid information in the IPO process. Finally, we examine the implications of flipping and find that although flipping increases liquidity, it contributes to stock price volatility and causes downward pressure on the stock price.